Quality of life and sociodemographic factors associated with poor quality of life in elderly women in Thiruvananthapuram, Kerala - R S Rajasi; Thomas Mathew; Zinia T Nujum; T S Anish; Reshmi Ramachandran; Tony Lawrence (Wolters Kluwer Medknow Publications, 2016)
Background: India is going through a phase of demographic transition leading to population aging and feminization of aging resulting in increased proportion of elderly women than men. Problems faced by the elderly women are more critical than men due to family and social conditions prevailing in India. Objective: The study made an attempt to assess the quality of life (QOL) using the World Health Organization QOL (WHOQOL-BREF) scale and sociodemographic factors affecting QOL of elderly women residing in a community setting in South Kerala. Methods: A community-based, cross-sectional study to assess the QOL of elderly women using WHOQOL-BREF questionnaire. Data were collected from 160 elderly women. Results: 2.5% (95% confidence interval [CI]: 0.07-4.84) of the study participants were having "very good" QOL. 38.8% (95% CI: 31.2-46.4) had "good," 43.1% (95% CI: 35.4-50.8) had "poor," and 15.6% (95% CI: 9.98-21.22) had "very poor" QOL, respectively. QOL was least in the psychological domain followed by physical and health-related, social, and environmental domains. Logistic regression revealed age above 70 years (adjusted odds ratio [OR] - 11.3), nonpossession of property (adjusted OR - 8.99), neglecting attitude by family (adjusted OR - 6.9), and absence of visit by friends and relatives (adjusted OR - 9.9) as risk factors, whereas residing in the urban area as a protective factor (adjusted OR - 0.1) for poor QOL. Conclusion: It is possible to improve the QOL of elderly women by providing financial security, ensuring care, and by enhancing social relationships of elderly women.